Influences of Au ion radiation on microstructure and surface-enhanced Raman scattering of nanoporous copper. (8th March 2018) - Wang, Jing; Hu, Zhaoyi; Li, Rui; Liu, Xiongjun; Xu, Chuan; Wang, Hui; Wu, Yuan; Fu, Engang; Lu, Zhaoping
Abstract: In this work, effects of Au ion irradiation on microstructure and surface-enhanced Raman scattering (SERS) performance of nanoporous copper (NPC) were investigated. It is found that the microstructure of NPC could be tailored by the ion irradiation dose, i.e., the pore size decreases while the ligament size significantly coarsens with the increase of the irradiation dose. In addition, the SERS enhancement for rhodamine 6G molecules was improved by Au ions irradiation at an appropriate dose. The underlying mechanism of the increase of SERS enhancement resulted from ion irradiation was discussed. Our findings could provide a new way to tune nanoporosity of nanoporous metals and improve their SERS performance.